Global Regulatory DNA Potentiation by SMARCA4 Propagates to Selective Gene Expression Programs via Domain-Level Remodeling - John E. Lazar; Sandra Stehling-Sun; Vivek Nandakumar; Hao Wang; Daniel R. Chee; Nicholas P. Howard; Reyes Acosta; Douglass Dunn; Morgan Diegel; Fidencio Neri; Andres Castillo; Sean Ibarrientos; et al. (Cell Reports, 2020)
Summary: The human genome encodes millions of regulatory elements, of which only a small fraction are active within a given cell type. Little is known about the global impact of chromatin remodelers on regulatory DNA landscapes and how this translates to gene expression. We use precision genome engineering to reawaken homozygously inactivated SMARCA4, a central ATPase of the human SWI/SNF chromatin remodeling complex, in lung adenocarcinoma cells. Here, we combine DNase I hypersensitivity, histone modification, and transcriptional profiling to show that SMARCA4 dramatically increases both the number and magnitude of accessible chromatin sites genome-wide, chiefly by unmasking sites of low regulatory factor occupancy. By contrast, transcriptional changes are concentrated within well-demarcated remodeling domains wherein expression of specific genes is gated by both distal element activation and promoter chromatin configuration. Our results provide a perspective on how global chromatin remodeling activity is translated to gene expression via regulatory DNA.